2020
DOI: 10.1515/ijfe-2019-0271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave-drying on the quality and antioxidant properties of Ganoderma lucidum fermented sea-buckthorn tea

Abstract: Effects of microwave power on the sensory properties (taste and aroma), chemical composition (catechins, caffeine, crude protein, and amino acid), active composition (flavones, triterpene, polysaccharide, and ergosterol) and antioxidant properties (superoxide free radical and hydroxyl radical scavenging abilities, reducing power) of Ganoderma lucidum fermented sea-buckthorn tea were investigated. G. lucidum fermented sea-buckthorn tea was dehydrated using microwaves at three power settings: 125, 250, and 500. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…MOPS was formulated into different mass concentration gradients, and their antioxidant activities were determined by the DPPH [ 21 ] method, ABTS [ 22 ] method, and reducing power method [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…MOPS was formulated into different mass concentration gradients, and their antioxidant activities were determined by the DPPH [ 21 ] method, ABTS [ 22 ] method, and reducing power method [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The process minimizes the loss of heat-sensitive bioactive compounds. It also provides a fiber-rich juice, showing great promise for processing sea buckthorn juice in the food industry ( 109 ). Sea buckthorn is rich in nutrients and bioactive compounds.…”
Section: Food Applicationsmentioning
confidence: 99%
“…Their oxidative activity and α-glucosidase inhibitory activity gradually increased with fermentation level (PTPS-5 > PTPS-3 > PTPS-1) [ 55 ]. Xin et al investigated the effect of different microwave powers on the antioxidant properties (superoxide radicals) of sea buckthorn TPS and showed that 250 W microwave treatment can effectively release and activate the active components in TPS and improve the antioxidant activity of fermented tea [ 56 ]. Li et al investigated the chemical composition and antioxidant activity of Yin Shan Yun Wu TPS and showed that GTPs have a molecular weight of 9.69 × 104 Da and consists of rhamnose, arabinose, xylose, mannose, glucose, and galactose (molar ratio; 11.4:26.1:1.9:3:30.7:26.8).…”
Section: Bioactivitymentioning
confidence: 99%